Association of soil bacterial diversity and composition with Fusarium wilt disease of bananas in Yogyakarta Province, Indonesia - IRIANTI KURNIASARI; ARIF WIBOWO; SITI SUBANDIYAH; ANTHONY B. PATTISON (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kurniasari I, Wibowo A, Subandiyah S, Pattison AB. 2024. Association of soil bacterial diversity and composition with Fusarium wilt disease of bananas in Yogyakarta Province, Indonesia. Biodiversitas 25: 2264-2275. Infection of banana plants with Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc-TR4) leads to a cascade of changes in the rhizosphere, resulting in changes to the soil physicochemical properties and bacterial community composition. This study aimed to determine the core taxa associated with different soil physicochemical properties and disease statuses and to identify the factors exerting the greatest influence on the soil bacterial community composition of bananas in Special Region of Yogyakarta Province, Indonesia. Rhizospheric soil from healthy and infected plants was collected from four banana locations, including Kulon Progo, Gunungkidul, Bantul, and Sleman districts, at 10-30 cm depth between May and September 2021. Laboratory analysis was conducted for soil physicochemical properties, and the abundance of Foc-TR4 was undertaken. Additionally, 16S rRNA gene-based metagenomics analysis was used to quantify bacterial diversity in all samples. Soil type significantly influenced the abundance and composition of the bacterial community more than disease status did. Contrarily, disease status groups influenced the complexity of bacterial network interaction more than soil type. Actinobacteriota, Proteobacteria, Chloroflexi, Acidobacteriota, and Bacteriodota are the major phyla associated with all soils. This study identified 60 bacterial genera as core members of the banana rhizosphere. These core bacterial genera include various plant growth-promoting bacteria involved in nitrogen fixation, phytohormone production, siderophore production, and biocontrol mechanisms for producing antifungal compounds. Our work provides a basis for future research on the soil bacterial composition associated with banana plants to enhance plant health against Fusarium wilt disease.